High-Rate Solid-Liquid Separation Coupled With Nitrogen and Phosphorous Treatment of Swine Manure: Effect on Ammonia Emission - Ro, Kyoung S.; Vanotti, Matias B.; Szogi, Ariel A.; Loughrin, John H.; Millner, Patricia D. (Frontiers in Sustainable Food Systems, 2018)
A new treatment system was developed to meet multiple environmental performance standards including to substantially reduce ammonia emissions. It was tested full-scale for 2-years in a 5,145-head finishing swine farm with two anaerobic lagoons. The system combined high-rate solid-liquid separation with nitrogen and phosphorus removal processes. Both vertical radial plum mapping (VRPM) and floating static chamber techniques were used to measure NH3 emission fluxes from anaerobic storage lagoons and the total farm-level NH3 emission rates. The VRPM used an open-path tunable diode laser absorption spectroscopy (TDL) and the flux chamber used a photoacoustic gas analyzer to accurately measure NH3 concentration. After the treatment system started, one of the two lagoons became inactive without receiving anymore flushed manure. The ammonia emission flux from the other lagoon with the treated effluent decreased from 43.9 to 6.8 kg-N ha−1 d−1 1.5 years after implementation of the new treatment system. The NH3 emission flux from the inactive lagoon also decreased similarly because the already stored old manure of the lagoon prior to inactivation was diluted with rainfalls and lost some NH3 via volatilization. The total farm-level NH3 emission rates decreased from 1.72 g s−1 to below detection level of the VRPM technique. Using the minimum detection level of the TDL with R2 > 90% (i.e., 8.1 8.1 μL L−1-m), the total farm-level NH3 emission rates in the second year were less than 0.04–0.15 g s−1. These results suggested that the impact of the new treatment system on NH3 emission reduction was equivalent to closing conventional swine lagoons while actively growing 5,145 pigs with minimal ammonia emissions from the farm.